Dare to serve : how to drive superior results by serving others - Bachelder, Cheryl (Berrett-Koehler Publishers, 2018)
This expanded and revised edition describes how to transform an ailing company into an industry darling, by adopting servant leadership. The author and former Popeyes CEO shows that leading by serving is a rigorous and tough-minded approach that yields the best results, and illustrates how that was accomplished at Popeyes.